IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION OF THE COMPONENTS DRINKING WATER MODEL: IDENTIFICATION - N., Loudjani*; A, Messaessa; A .T, . Bouzain (university of eloued جامعة الوادي, 2020)
In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box In this paper, we consider the modeling of time series corresponding to methodology Box and Jenkins forand Jenkins for and Jenkins for and Jenkins for and Jenkins forand Jenkins for building building forecasting forecasting forecasting forecasting forecasting forecasting modeling odeling odeling from ARMA ( from ARMA (from ARMA ( from ARMA ( from ARMA (from ARMA (Auto Regressive Mov Auto Regressive MovAuto Regressive MovAuto Regressive Mov Auto Regressive Mov Auto Regressive Mov Auto Regressive Mov ing Average) ing Average)ing Average) ing Average) ing Average)ing Average)ing Average) processes. This involves the analysis and forecas processes. This involves the analysis and forecasprocesses. This involves the analysis and forecas processes. This involves the analysis and forecas processes. This involves the analysis and forecas processes. This involves the analysis and forecas processes. This involves the analysis and forecasprocesses. This involves the analysis and forecasprocesses. This involves the analysis and forecas processes. This involves the analysis and forecasprocesses. This involves the analysis and forecas processes. This involves the analysis and forecas processes. This involves the analysis and forecas processes. This involves the analysis and forecasprocesses. This involves the analysis and forecas processes. This involves the analysis and forecas processes. This involves the analysis and forecasprocesses. This involves the analysis and forecasprocesses. This involves the analysis and forecasprocesses. This involves the analysis and forecasting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The ting of drinking water production data. The purpose of this study is to model purpose of this study is to model purpose of this study is to modelpurpose of this study is to model purpose of this study is to model purpose of this study is to model purpose of this study is to model purpose of this study is to modelpurpose of this study is to modelpurpose of this study is to model purpose of this study is to model purpose of this study is to modelpurpose of this study is to model ing a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to a time series of drinking water production data according to its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values its past and present values in order to determine in order to determine in order to determine in order to determine in order to determine in order to determine in order to determine in order to determine in order to determine the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of the adequate ARMA process by principle of parsimony. Using parsimony. Using parsimony. Using parsimony. Using the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of the Eviews for Windows software, results show that exploration of monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority monthly drinking water consumption data provided by the Biskra Management Authority (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period (A.D.E) during the period from Janu from Janu from Janu from Janu aryary 2009 to January to Januaryto Januaryto January to January 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as 2016, Revealed characteristics such as the non -stochastic non stochastic non stochastic nonstochastic non -stationarity of the drinking water production series. stationarity of the drinking water production series.stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series.stationarity of the drinking water production series.stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity of the drinking water production series. stationarity
ARTICAL
Keywords: Keywords:Keywords: Time series; Box and JenkinsTime series; Box and Jenkins Time series; Box and JenkinsTime series; Box and Jenkins Time series; Box and JenkinsTime series; Box and Jenkins Time series; Box and Jenkins Time series; Box and JenkinsTime series; Box and Jenkins Time series; Box and Jenkins Time series; Box and Jenkins method ; ARMA process; Eviews software. ; ARMA process; Eviews software. ; ARMA process; Eviews software. ; ARMA process; Eviews software.; ARMA process; Eviews software.; ARMA process; Eviews software. ; ARMA process; Eviews software. ; ARMA process; Eviews software. ; ARMA process; Eviews software. ; ARMA process; Eviews software.